ANALISIS KEBUTUHAN PESERTA DIDIK TERHADAP MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI ARITMATIKA SOSIAL SMP - Tedi Setiadi; Kiki Nia Sania Effendi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this study is to analyze the needs of students for android-based learning media in junior high school social arithmetic materials that can support limited face-to-face learning. The research subjects were 20 students of class VIII SMPN 1 Rawamerta, Karawang. This research is a qualitative descriptive research. The research instrument used was an interview guide and a questionnaire on the needs of students. The results of this study are in the form of data obtained from observations, interviews with one of the mathematics teachers, and also a questionnaire filled out by the research subjects. The data analysis technique used refers to the Miles and Huberman model, namely (1) data reduction (data collection), (2) data presentation, and (3) drawing conclusions. From the results of the study, it was concluded that 1) Social arithmetic is a mathematical material that is considered difficult by students, 2) Students need practical learning media, and 3) educators and students agree when developing Android-based learning media on social arithmetic material.